Plasma Exosomal Mir-423-5p Is Involved in the Occurrence and Development of Bicuspid Aortopathy via TGF-β/SMAD2 Pathway - Zhang, Hongqiang; Liu, Dingqian; Zhu, Shichao; Wang, Fanshun; Sun, Xiaoning; Yang, Shouguo; Wang, Chunsheng (Frontiers in Physiology, 2021)
Objectives: Patients with bicuspid aortic valve (BAV) are at increased risk for ascending aortic dilation (AAD). Our study was aimed at systemically analyzing the expression profile and mechanism of circulating plasma exosomal microRNAs (miRNAs) related to BAV and AAD. Methods: We isolated plasma exosomes from BAV patients (n=19), BAV patients with AAD (BAVAD, n=26), and healthy tricuspid aortic valve individuals with low cardiovascular risk (TAVnon, n=16). We applied a small RNA sequencing approach to identify the specific plasma exosomal miRNAs associated with BAV (n=8) and BAVAD (n=10) patients compared with healthy TAVnon (n=6) individuals. The candidate differentially expressed (DE) miRNAs were selected and validated by RT-qPCR in the remaining samples. GO and KEGG pathway enrichment analyses were performed to illustrate the functions of target genes. Western blot analysis and luciferase reporter assay were conducted in human aortic vascular smooth muscle cells (VSMCs) to verify the results of target gene prediction in vitro. Results: The expression levels of three up-regulated (miR-151a-3p, miR-423-5p, and miR-361-3p) and two down-regulated (miR-16-5p and miR-15a-5p) exosomal miRNAs were significantly altered in BAV disease. Additionally, miR-423-5p could be functionally involved in the occurrence and development of BAV and its complication BAVAD by regulating TGF-β signaling. miR-423-5p could target to SMAD2 and decreased the protein levels of SMAD2 and P-SMAD2. Conclusion: Plasma exosomal miR-423-5p regulated TGF-β signaling by targeting SMAD2, thus exerting functions in the occurrence and development of BAV disease and its complication bicuspid aortopathy.